Micro Teaching as a Teacher's Weapon Against Digital Distraction - Vani Zakiyah; Euis Latifah; Muhammad Makbul Fauzan; M. Ryan Fauzi (Classroom: Journal of Islamic Education, 2025)
The development of digital technology has brought about major changes in the world of education, both in terms of ease of access to information and new challenges, such as increasing digital distractions in the classroom. The use of devices such as mobile phones and laptops often distracts students from learning materials. To overcome this, teachers need to have effective and adaptive teaching strategies. One relevant approach is micro teaching, a small-scale teaching training method that focuses on improving pedagogical skills and classroom management. This article discusses how micro teaching can equip teachers to deal with digital distractions through structured, reflective, and practice-based exercises. Theoretical studies and case studies show that teachers who take part in micro teaching training tend to be better prepared to face the challenges of the digital classroom, and are able to create a more focused, interactive, and productive learning environment.